Аdvancing International Competitiveness аs а Factor оf Development оf Industrial Enterprise - Ярош-Дмитренко, Людмила Олексіївна (Київський національний університет імені Тараса Шевченка, 2017)
У статті проблема підвищення міжнародної конкурентоспроможності промислового підприємства висвітлюється в контексті забезпечення можливостей для подолання кризових явищ в країні та формування передумов економічного зростання. Представлено та проаналізовано систему факторів, визначено пріоритети підвищення міжнародної конкурентоспроможності промислових підприємств, які визначають можливості позитивного впливу на подолання кризових явищ в економіці.

In the article the problem of advancing the international competitiveness of industry has been highlighted in the context of the impact on getting out the crises in the country and forming preconditions for economic growth. The study is based on an empirical basis of metallurgical industries of Ukraine, which has traditionally focused largely on international markets. The advancing international competitiveness of these enterprises is particularly topical and important for getting over the crisis and forming a trajectory of economic development of the country. The system of the factors has been represented and analysed, the priorities for advancing the international competitiveness of metallurgical industryJSC "Zaporizhstal".Recommendations to improve the competitiveness of the analysed enterprise have been formulated and common priorities for improving the international competitiveness of steel companies determining the possibility of positive impact on getting over the crisis and economic development at the level of companies, as well as at the level of Ukraine's economy have been identified.
Підвищення міжнародної конкурентоспроможності як фактор розвитку промислового підприємства
Keywords: міжнародна конкурентоспроможність; конкурентна перевага; промислове підприємство; закордонні ринки; міжнародний ринок; експорт; економічний розвиток; кризові явища; international competitiveness; competitive advantage; industrial enterprise; foreign markets; international market; export; economic development; crises